Material didáctico de reciclaje en el pensamiento lógico matemático en los niños de primer grado de educación básica, paralelo “A” en la unidad educativa “Riobamba”, de la ciudad de Riobamba, provincia de Chimborazo, año lectivo 2016 – 2017 - Freire Yambay, Tatiana Maribel (2016)
The present work of research is about the importance Didactic Material of Recycling in the Mathematical Logical Thinking in the children of first grade of Basic Education in the Educational Unit "Riobamba" is evidenced, the develop Mathematical Logical Thinking in the children and to identify the benefits of the use of Recycling and the dependent that is the mathematical logical thinking. Within the methodology used for the accomplishment of the present work was considered the scientific method, deductive inductive, documentary, information was collected from 18 to 15 children with a Total of 33 students who were observed and made an observation sheet, which was tabulated and analyzed; It is concluded that the characteristics of didactic recycling materials such as accessibility, diversification, use and employment are determinant for the child is able to manipulate it, create and construct new elements to help him in the development of mathematical logical thinking in first grade. It is recommended the use of didactic material of recycle, because it supports the development of the logical thinking of the children of first grade, beside it is invaluable based on psycho-cognitive theory can be established that the manipulation of varied objects allows to materialize an abstract learning.